Do Governmental Tax Reliefs for Investment Lead to Investment Efficiency and Sustainability for SMEs? Evidence From South Korea - Hyeongtae Cho; SungMan Yoon (SAGE Open, 2023)
Tax credits for investment in productivity enhancement facilities, R&D facilities, and employment-creating initiatives are available to corporate taxpayers in Korea. These incentives are intended to motivate corporations to invest by providing financial support to improve their efficiency and help sustain their survival. This study aims to analyze whether corporations that claim investment tax credits (ITCs) in Korea actually achieve investment efficiency and increase corporate value. This study’s results are as follows. First, based on the statistical analysis of samples from small- and medium-sized enterprises (SMEs) and all corporations, we find empirical evidence that investments through claimed tax credits are inefficient from the standpoint of Tobin’s Q . This finding may be interpreted to mean that corporate taxpayers, including SMEs, consider tax savings more than investment efficiency in claiming ITCs. Second, in testing the investment efficiency for each ITC, we find that SMEs’ investment via employment-creating ITCs is more efficient than other investments with tax credits. This finding implies that SMEs should not only invest in physical facilities, but also retain human resources for sustainability. These results provide policy implications that employment creation should be considered when granting ITCs for SMEs’ efficient investments.